UMP research products won 5 medals at BioMalaysia 2009 - UMP, PNC
University Malaysia Pahang’s (UMP) participation in the BioMalaysia Conference & Exhibition 2009, held at the Kuala Lumpur Convention Centre on November 17-19 last year, bore fruits when the university successfully brought home two gold and three bronze medals for its research and development products.